MEKANISME PERTAHANAN DIRI TOKOH UTAMA PADA NOVEL PUKUL SETENGAH LIMA KARYA TSANA - Yunita Sari; Elsa Mulya Karlina (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study aims to reveal the forms of self-defense mechanisms experienced by the main character in the novel Pukul Setengah Lima by Tsana. The problem in this study focuses on how the main character deals with emotional conflicts that arise due to traumatic experiences in the past. This study uses a qualitative approach with a type of library research. Primary data comes from the text of the novel Pukul Setengah Lima, while secondary data is in the form of theoretical literature from Sigmund Freud and Anna Freud, as well as relevant scientific studies. Data collection techniques are carried out through documentation studies and reading and notes, then analyzed using qualitative descriptive analysis with a psychoanalytic approach. The results of the study show that the main character uses seven forms of self-defense mechanisms, namely repression, rationalization, recognition, fixation, projection, reaction formation, and sublimation. Each form of protection appears in response to psychological pressure and inner tension experienced by the main character. These findings indicate that literary works can represent human psychological dynamics in depth and become a means of reflection on the individual's mental condition in dealing with trauma and emotional stress.